Bioimpedance measurement based evaluation of wound healing. (22nd June 2017) - Kekonen, Atte; Bergelin, Mikael; Eriksson, Jan-Erik; Vaalasti, Annikki; Ylänen, Heimo; Viik, Jari
Abstract: Objective : Our group has developed a bipolar bioimpedance measurement-based method for determining the state of wound healing. The objective of this study was to assess the capability of the method. Methods : To assess the performance of the method, we arranged a follow-up study of four acute wounds. The wounds were measured using the method and photographed throughout the healing process. Results : Initially the bioimpedance of the wounds was significantly lower than the impedance of the undamaged skin, used as a baseline. Gradually, as healing progressed, the wound impedance increased and finally reached the impedance of the undamaged skin. Conclusion : The clinical appearance of the wounds examined in this study corresponded well with the parameters derived from the bioimpedance data. Significance : Hard-to-heal wounds are a significant and growing socioeconomic burden, especially in the developed countries, due to aging populations and to the increasing prevalence of various lifestyle related diseases. The assessment and the monitoring of chronic wounds are mainly based on visual inspection by medical professionals. The dressings covering the wound must be removed before assessment; this may disturb the wound healing process and significantly increases the work effort of the medical staff. There is a need for an objective and quantitative method for determining the status of a wound without removing the wound dressings. This study provided evidence of the capability of the bioimpedance based method for assessing the wound status. In the future measurements with the method should be extended to concern hard-to-heal wounds.